Analysis Of The Effect Of Workload And Work Environment On Employee Satisfaction And Performance PT XYZ Using SEM - Aisyah Elvina, Helga; Waluyo, Minto (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine whether there is an influence between workload and work environment on employee satisfaction and performance at PT XYZ. The sample of this study was 122 employees who were directly involved in operations. and the method applied was SEM. The results of this study are that workload and work environment significantly influence employees' job satisfaction. workload and work environment have a significant effect on employee performance. Furthermore, employee satisfaction has a notable effect on employee performance. For further research, it is recommended to expand the variables studied.